Diagnosis and Therapeutic Management of Canine Demodicosis in Saurashtra Region of Gujarat - Satasiya, Chintan G.; Vagh, Arshi A.; Bilwal, Awinash K.; Bhatt, Raghuvir H.; Parasana, Dixit K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Among 23 dogs positive with canine demodicosis, 18 were selected for study, and 6 healthy dogs were taken as control. The dogs were divided into 4 groups, each consisting of 6 animals. Group I served as control. Group II, III and IV were treatment groups. Dogs of group II were given a subcutaneous injection of ivermectin @ 0.2 mg/kg b.wt weekly up to 4 weeks in combination with topical application of amitraz 12.5% solution as 0.05% mixed in water. Dogs of group III were given safrone tablets PO for 10 days in combination with safrone oil topically for 15 days. Dogs of group IV were given a fluralaner tablet @ 25 mg/kg PO for a single dose. All the dogs were bathed with shampoo containing benzoyl peroxide at weekly interval, except dogs of group III, and were given cefpodoximeproxetil @ 10 mg/kg b.wt. and pheniramine maleate @ 1 mg/kg b.wt. PO bid for 5 days and vitabestderm syrup 5 mL PO bid. Serum interleukin (IL)-10 showed a significant or appreciable increase in demodectic animals compared to healthy animals. Mite count was reduced up to 100 % on 30th day post-treatment in dogs of group II and there was quite a reduction in mite count in dogs of group IV, while lowest reduction in mite count was noticed 30th day post-treatment in dogs of group III. So, it was concluded that a combination of injection of ivermectin subcutaneously and amitraz 12.5% solution diluted to 0.05% topically had the highest efficacy among 3 treatment protocols used for canine demodicosis.